Type I and type II residual stress in iron meteorites determined by neutron diffraction measurements. (April 2018) - Caporali, Stefano; Pratesi, Giovanni; Kabra, Saurabh; Grazzi, Francesco
Abstract: In this work we present a preliminary investigation by means of neutron diffraction experiment to determine the residual stress state in three different iron meteorites (Chinga, Sikhote Alin and Nantan). Because of the very peculiar microstructural characteristic of this class of samples, all the systematic effects related to the measuring procedure - such as crystallite size and composition - were taken into account and a clear differentiation in the statistical distribution of residual stress in coarse and fine grained meteorites were highlighted. Moreover, the residual stress state was statistically analysed in three orthogonal directions finding evidence of the existence of both type I and type II residual stress components. Finally, the application of von Mises approach allowed to determine the distribution of type II stress. Highlights: Residual stress determination via neutron diffraction in three iron meteorites. Evidence of type I and type II residual stress in Chinga meteorite. Statistical distribution of von Mises type II stress.